Diagnosis of mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes in a Chinese family by PCR/restriction enzyme analysis. Issue 5 (October 1995) - Lam, C W; Jain, K; Chan, K Y; Silva, D K; Chan, Y W; Wong, L J C
Abstract : The clinical presentation and the biochemical and molecular genetic findings are described in a 13 year old Chinese boy with MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes). The diagnosis was initially suspected because of the characteristic clinical features and the strong family history of convulsions. Using polymerase chain reaction—restriction enzyme analysis, the heteroplasmic nt3243 A→G mutation in mtDNA of peripheral blood leucocytes and a muscle sample was demonstrated. The oligosymptomatic relatives were then screened by this method and the degree of heteroplasmy was analysed. This appears to be the first report of a MELAS family in Hong Kong with this described mutation. Molecular genetic techniques are advantageous in the diagnosis of MELAS.